Less bang for the buck? Assessing the role of inflation uncertainty for U.S. monetary policy transmission in a data rich environment - Helmut Herwartz; Hannes Rohloff (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
We investigate the relationship between inflation uncertainty and monetary policy transmission in the U.S. economy. Monetary policy shocks are identified within the framework of nonlinear structural factor-augmented VARs which allow us to analyze several complementary hypotheses connecting IU with reduced monetary policy effectiveness. We find that the real effects of monetary policy shocks are markedly dampened conditional on high IU. This can be traced back to, inter alia, real-option and precautionary savings effects which distort the traditional interest rate channel. Moreover, policy transmission through the external finance premium and the term structure of interest rates appears strongly dependent on inflation uncertainty and contributes to the reduced policy effectiveness.
Keywords: C32; E44; E52; 330; inflation uncertainty; SVAR; monetary policy; sign restrictions; asset prices; smoothtransition